Current corticosteroid therapeutic strategy for community-acquired pneumonia in adults: indications, dosage, and timing - Seitaro Fujishima (Journal of Intensive Care)
Abstract Despite advances in treatment and the expansion of standard care, pneumonia remains a major cause of mortality. It frequently leads to complications such as septic shock and acute respiratory distress syndrome (ARDS), both of which carry high fatality rates. Although antimicrobial therapy is the cornerstone of treatment, additional supportive care and adjunctive therapies, such as corticosteroids, are often required, especially in severe community-acquired pneumonia (CAP). Recent updates to major guidelines on CAP, sepsis, ARDS, and critical illness-related corticosteroid insufficiency generally support corticosteroid use in severe CAP. However, the REMAP-CAP randomized controlled trial, published in 2025, failed to demonstrate significant benefit, potentially influencing future recommendations. Currently, corticosteroid therapy should be individualized based on CAP severity, particularly the degree of hypoxemia and respiratory failure. In eligible patients, early initiation and flexible duration of corticosteroid use based on clinical response may be appropriate. For nonbacterial pneumonia, strong evidence supporting corticosteroid use exists only for COVID-19 and Pneumocystis jirovecii pneumonia in HIV-infected individuals. Conversely, observational data do not support corticosteroid use for influenza or fungal infections. In CAP complicated by septic shock or ARDS, corticosteroid use is endorsed by recent guidelines; however, the recommended timing, dosage, and duration vary. Although combination therapy with hydrocortisone and fludrocortisone is a potential option, further direct evidence is needed. Biomarkers such as C-reactive protein and, in the near future, insights into corticosteroid-related immune repair mechanisms in COVID-19 may aid in identifying corticosteroid-responsive phenotypes.